Seroprevalence of hepatitis B virus infection in individuals with clinical evidence of hepatitis in Goiânia, Goiás: detection of viral DNA and determination of subtypes - Claudia de Oliveira e SILVA; Marli da Silva Pereira AZEVEDO; Célia Maria de Almeida SOARES; Regina Maria Bringel MARTINS; Carmen Helena RAMOS; Roberto Ruhman DAHER; Divina das Dôres de Paula CARDOSO (Universidade de São Paulo (USP), 2002)
The presence of serological markers for hepatitis B virus (HBsAg, anti-HBc IgM and Anti-HBc total) was investigated in the serum of 1,396 individuals who had clinical suspect of hepatitis. It was observed that 50.7% of the individuals were positive and, from the total of the studied individuals, 14.5% were positive for HBsAg. From these, 8.5% were also positive for anti-HBc IgM. The analysis in relation to gender showed a higher seroprevalence index among male individuals (p < 0.0001). It was observed the occurrence of subtypes adw2 (62.7%), ayw3 (23.5%), ayw2 (9.8%) and adw4 (3.9%). The viral DNA was detected in 61 (33.9%) HBsAg positive samples and in one sample positive only for anti-HBc total. These results indicate an important incidence of the HBV infection in this population, and reinforce previous studies regarding this virus in the central west region of Brazil.